WormBase in 2022—data, processes, and tools for analyzing Caenorhabditis elegans. Issue 4 (4th February 2022) - Davis, Paul; Zarowiecki, Magdalena; Arnaboldi, Valerio; Becerra, Andrés; Cain, Scott; Chan, Juancarlos; Chen, Wen J; Cho, Jaehyoung; da Veiga Beltrame, Eduardo; Diamantakis, Stavros; Gao, Sibyl; Grigoriadis, Dionysis; et al.
Abstract: WormBase (www.wormbase.org ) is the central repository for the genetics and genomics of the nematode Caenorhabditis elegans . We provide the research community with data and tools to facilitate the use of C. elegans and related nematodes as model organisms for studying human health, development, and many aspects of fundamental biology. Throughout our 22-year history, we have continued to evolve to reflect progress and innovation in the science and technologies involved in the study of C. elegans . We strive to incorporate new data types and richer data sets, and to provide integrated displays and services that avail the knowledge generated by the published nematode genetics literature. Here, we provide a broad overview of the current state of WormBase in terms of data type, curation workflows, analysis, and tools, including exciting new advances for analysis of single-cell data, text mining and visualization, and the new community collaboration forum. Concurrently, we continue the integration and harmonization of infrastructure, processes, and tools with the Alliance of Genome Resources, of which WormBase is a founding member.